Efeitos da associação da clonidina à bupivacaína hiperbárica na anestesia subaracnóidea alta - Braz, José Reinaldo Cerqueira [UNESP]; Koguti, Edgar Shiguero [UNESP]; Braz, Leandro Gobbo [UNESP]; Croitor, Lorena Brito da Justa [UNESP]; Navarro, Lais Helena Camacho [UNESP] (My University, 2003)
BACKGROUND AND OBJECTIVES: Published data suggest that clonidine, an α2-adrenergic agonist, in association with bupivacaine, may increase the incidence of intraoperative hypotension and bradycardia during high-level spinal anesthesia. This study aimed at determining the synergistic potential of two clonidine doses (45 and 75 μg) and hyperbaric bupivacaine on. characteristics and hemodynamic effects of high-level (T4) spinal anesthesia. METHODS: Participated in this randomized double-blind study, 60 ASA I patients scheduled for lower abdominal and limb surgery. Spinal anesthesia was induced with 17.5 mg (3.5 ml) of 0.5% hyperbaric bupivacaine plus the association of the following drugs: Control group (n = 20) - 0.5 ml isotonic saline solution; Clon 45 group (n = 20) - 45 μg (0.3 ml) clonidine + 0.2 ml isotonic saline solution; and Clon 75 (n = 20) - 75 μg (0.5 ml) clonidine. Surgery was only started when high-level (T4) analgesia was consistently obtained, RESULTS: Sensory and motor block onset did not significantly differ among groups (p > 0.05). Both clonidine doses significantly prolonged analgesic block at T8 and motor block level 3 duration (determined by modified Bromage scale) (p < 0.05). Intraoperative arterial hypotension was observed only in Clon 75 group as compared to Control group (p < 0.05), while Clon 45 group had intermediate incidence between both groups. There was no significant difference among groups in bradycardia (p > 0.05). Both clonidine doses prolonged postoperative analgesia (time from spinal block to first postoperative analgesic request) (p < 0.05). CONCLUSIONS: High clonidine dose (75 μg) associated to hyperbaric bupivacaine during high-level spinal anesthesia (T4) induces a higher incidence of arterial hypotension but prolongs sensory block and postoperative analgesia similar to lower clonidine dose (45 pg) during upper spinal anesthesia.
Effects of clonidine associated to hyperbaric bupivacaine during high-level spinal anesthesia
Keywords: Analgesics: clonidine; Anesthetic techniques, Regional: spinal block; Anesthetics: Local: bupivacaine